Candida and Complement: New Aspects in an Old Battle - Harpf, Verena; Rambach, Günter; Würzner, Reinhard; Lass-Flörl, Cornelia; Speth, Cornelia (Frontiers in Immunology, 2020)
Candida is a dominant fungal pathogen in immunocompromised hosts, leading to opportunistic infections. Complement with its multifaceted functions is involved in the immune defense against this yeast, and recently several novel aspects have emerged in this old battle. It is clear that Candida can adopt both roles as a colonizer or as a pathogen. In our article, we focus on the molecular mechanisms of the Candida-complement interplay, which occur in disseminated disease as well as locally on skin or on mucous membranes in mouth and vagina; the mechanisms can be supposed to be the same. Activation of the complement system by Candida is facilitated by directly triggering the three dominant pathways, but also indirectly via the coagulation and fibrinolysis systems. The complement-mediated anti-Candida effects induced thereby clearly extend chemotaxis, opsonization and phagocytosis, and even the membrane attack complex formed on the fungal surface plays a modulatory role, although lysis of the yeast per se cannot be induced due to the thick fungal cell wall. In order to avoid the hostile action of complement, several evasion mechanisms have evolved during co-evolution, comprising the avoidance of recognition and destruction. The latter comes in many flavors, in particular the cleavage of complement proteins by yeast enzymes and the exploitation of regulatory proteins by recruiting them on the cell wall, such as factor H. The rationale behind that is that the fluid phase regulators on the fungal cell surface down-regulate complement locally. Interestingly, however, evasion protein knockout strains do not necessarily lead to an attenuated disease, so it is likely more complex in vivo than initially thought. The interaction between complement and non-albicans species also deserve attention, especially Candida auris, a recently identified drug-resistant species of medical importance. This is in particular worth investigating, as deciphering of these interactions may lead to alternative anti-fungal therapies directly targeting the molecular mechanisms.